Allograft nephrectomy vs. no nephrectomy for failed renal transplants - McDonald, Michelle (Frontiers in Nephrology, 2023)
The role of allograft nephrectomy (AN) in failed renal transplants is a topic of debate, owing to controversial results reported in the literature and the fact that most of the studies are limited by a retrospective design and small numbers of participants. Allograft nephrectomy is most likely of benefit in the patient with recurrent allograft intolerance syndrome (AIS) following pulse steroids. Immunosuppression weaning in the presence of clinical signs related to a chronic inflammatory state is also reasonable grounds to pursue AN. Studies are mainly inconclusive but suggest that AN has no overall benefit for allograft survival after retransplant. This topic is still of interest in the transplant field and is particularly relevant for patients who are likely to require retransplantation within their lifetime. Further assessment is needed in the form of randomized controlled trials that control for various AN indications and immunosuppression regimens, and have clearly defined survival outcomes.